2019
DOI: 10.1186/s12890-019-1011-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency among patients with pulmonary hypertension

Abstract: BackgroundThere is little information about vitamin D (Vit D) deficiency in patients with pulmonary hypertension (PH). The objective of this study was: 1) compare Vit D levels between patients with PH, left ventricular failure (LVF) and healthy subjects (HS); 2) correlate, in patients with PH, Vit D levels with prognosis-related variables, such as the 6-min walk test (6MWT).MethodsVitamin D levels were measured in a cross-sectional study in 126 patients from one of three groups: patients with PH (n = 53), pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Values were very similar for idiopathic (class 1.1) and heritable PAH (class 1.2), and the sample of the drug-induced PAH (class 1.3) was too small to draw any conclusion. In a recent published study, 25(OH)vitD levels from PH patients with different etiologies were also analyzed as a single group [34].…”
Section: Discussionmentioning
confidence: 99%
“…Values were very similar for idiopathic (class 1.1) and heritable PAH (class 1.2), and the sample of the drug-induced PAH (class 1.3) was too small to draw any conclusion. In a recent published study, 25(OH)vitD levels from PH patients with different etiologies were also analyzed as a single group [34].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent bone fractures, treatment of vitD deficiency is mandatory to restore calcium and bone homeostasis. Because lower 25(OH)vitD levels vitD are associated with worse prognosis in PAH patients [18,[20][21][22][23], we speculate that restoring vitD status may improve their lung pathology, besides improving their bone and muscular health.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we [18] and others [19][20][21][22][23] have demonstrated that vitD deficiency is much more frequent in PAH than in the general population. Insufficient levels, i.e., 25(OH)vitD < 20 ng/mL, are present in up to 95% of the patients and a severe deficit, i.e., 25(OH)vitD < 10 ng/mL, with subsequent secondary hyperparathyroidism is observed in 70% of them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are aware that the role of vitamin D is not just limited to bone health, however, its role outside bone health is poorly understood. Research has shown that vitamin D deficiency has a negative impact on morbidity and mortality outcomes in patients who have chronic illnesses such as heart disease, diabetes mellitus, cancer, pulmonary hypertension, and auto-immune disorders [ 4 - 5 ]. Unfortunately, none of the current evidence was able to explain the association between vitamin D deficiency and these chronic diseases.…”
Section: Introductionmentioning
confidence: 99%